APPRAISAL OF WORKPLACE SEXUAL HARASSMENTS IN NIGERIA: THE INADEQUACY OF THE EXTANT LAWS - Abubakar, Aliyu; Yahaya, Musa; Zanwa, Ahmad Aliyu (LexScriptio A Journal of the Department of Jurisprudence and Public Law, 2025)
Allegations of Sexual harassments in public offices in Nigeria is recently taking a disturbing dimension, with highly placed public officials  being indicted  to the extent of demanding sexual gratification from their colleagues in return for lucrative assignments, recognition or viable posting among other reasons. Various laws were enacted to address various offences in Nigeria inclusive of sexual harassments. However, there is no single comprehensive national legislation that addresses workplace sexual harassment in Nigeria. There is as well, plethora of court decisions sanctioning the acts of workplace sexual harassment in Nigeria, but those decisions cannot be comprehensive and exhaustive as the enabling laws were also not comprehensive or exhaustive. This paper appraised various provisions of the laws of sexual harassment in Nigeria side by side with the recent allegations of sexual harassments in the Senate of the Federal Republic of Nigeria, as it particularly affects the integrity of the Public Service of the Federation.. This paper observed that the laws seeking to punish the acts of sexual harassment in Nigeria are inadequate, and it is accordingly recommended that a single national comprehensive legislation should be enacted to address the disquieting development of sexual harassment in Nigeria public offices. This paper seeks to address the question, why should the Senate insists on passing the Sexual Offences Bill into law in 2020 against the lecturers in the tertiary educational institutions in the country while there is a skeleton in their cupboard? This paper adopts the use of doctrinal method of research.